Growth and Yield of Two Forage Legumes of Contrasting Growth Habits Under Shade - Sornprasitti, Pensri (2004)
A study was conducted to evaluate the responses of two forage legumes Arachis pintoi Krapov. & D. Gregory (Arachis) and Stylosanthes guianensis (Aublet) Sw. (Stylo), of contrasting growth habits (prostrate and erect type) to levels of shade. Treatments used over three experiments included three radiation regimes (30, 50 and 100% light transmission), two cutting intervals (6 and 8 week), two cutting heights (5 and 10 cm) and the removal of residual leaves on yield and growth of the plants. Both species had reduced yield with increased shading but Stylo showed greater reduction in yield with shade compared to Arachis. Under fill sunlight, Stylo performed better giving a 43 percent greater yield than Arachis. On the other hand, Arachis yielded 6 percent more than Stylo under both shaded treatments, indicating . . . 111 that the prostrate habit made the plant more tolerant to shading. Arachis also had a greater leaflstem ratio, and better nodulation under shade than Stylo. The better nodulation of Arachis under shade compared to Stylo may have attributed to the greater shade tolerance of Arachis. Both legumes were affected by cutting interval; the longer cutting interval of 8 weeks gave higher yield than the 6 weeks cutting interval (increase of 20.7 percent for Arachis and 36.5 percent for Stylo). On the other hand, nutritive quality was better for both legumes with the shorter cutting interval. Increased frequency of cutting reduced plant persistence of Stylo by 8.8 percent while that of Arachis increased by 26 percent, showing that the legumes with the prostrate habit is more tolerant to frequent cutting. Cutting height had significant effect on yield of Stylo and Arachis under shading, both giving higher yield under 10 cm cutting height than 5 cm cutting height. Stylo showed a greater reduction in yield (40%) than Arachis (17.1%) with the lower cutting height. This proved that the prostrate habit made the plant more tolerant of low cutting height than the upright habit. The presence of residual leaves was more important for regrowth of Arachis than for Stylo. In Stylo, plant regrowth was influenced by cutting height irrespective of the presence or absence of residual leaves. On the other hand, in Arachis, plants cut at the low cutting height gave similar regrowth with those at the higher cutting height as long as residual leaves are retained. In conclusion, the upright legume, Stylo was less tolerant to shading than the prostrate legume Arachis. The latter should be a more suitable legume for use under the integration system where forages are grown under the plantation crops. Arachis is also more tolerant to intensive defoliation as shown by its better ability to withstand shorter cutting interval and lower cutting height than Stylo.